INDICATORS OF THE BLOOD COMPOSITION OF MEDICATED HORSES - Suleimenov, Sh. K.; Dyusembayev, S. T.; Muratbayev, D. M. (Жәңгір хан атындағы БҚАТУ, 2024)
This study investigates hematological, biochemical indicators, and mineral content in the blood of horses affected by paraskaridosis, emphasizing the biochemical processes following therapeutic measures. Blood plays a critical role in maintaining the animal's health and reflecting the state of hematopoietic organs. The research involved three groups of Jabe breed horses infected with paraskarids, with one group serving as a control. Blood samples were collected before and 45 days after deworming. Results indicated significant changes in blood parameters due to parasitic infestation, particularly in hemoglobin, red blood cells, white blood cells, and mineral levels. Hemoglobin levels dropped by 23.5-36%, while erythrocyte counts were also reduced in infested horses. After treatment, hemoglobin and erythrocyte levels were restored. Biochemical analysis revealed lower total protein and glucose levels in infected horses, along with significant reductions in urea, bilirubin, phosphorus, magnesium, iron, sodium, potassium, and chloride. Overall, these findings highlight the impact of paraskaridosis on horse health and the importance of monitoring blood parameters for assessing recovery and overall well-being.
Suleimenov , Sh. K. Іndicators of the blood composition of medicated horses / Sh. K. Suleimenov , S. T. Dyusembayev, D. M. Muratbayev. - Текст : непосредственный // Ғылым және білім=Наука и образование=Science and education. - 2024. - № 4-1 (77). - Р. 248-256 (Uralsk).
Keywords: Paraskaridosis; hematological indicators; biochemical indicators; horse health; blood composition; deworming; mineral content; therapeutic measures